Comparative Analysis of Terrestrial Gastropod Molluscs of the Molguzar Mountains (Uzbekistan) - Gaibnazarova Feruza Pardabaevna; Urazboyeva Dilrabo (American Journal of Biology and Natural Sciences, 2026)
This article present a comparative analysis of terrestrial gastropod molluscs recorded from the Molguzar Mountains (north-western Turkestan Range). Species composition, taxonomic structure, ecologic groups, biotopic distribution and altitudinal zonation were analyzed based on long-term field studies and literature data. The result show dominance of xerophilous and xeromesophilous species adapted to arid mountain conditions.